Zaburzenia rozwoju mowy a trudności w czytaniu i pisaniu. Analiza przypadku osoby z alalią - Dębińska-Gustaw, Kamila (Logopedia Silesiana, 2015)
Reading and writing skills are necessary for the proper functioning of human society, there are one of the forms of linguistic communication. Underlying the difficulty in mastering these skills may lie among others speech disorders, including neurological substrate. In the case of people with alalia, developmental disorders of speech significantly affect the mastery of reading and writing. There are language operations in which the symptoms of disorder may persist for a long time. The article discusses the relation of speech disorders of neurological substrate with difficulties in reading and writing. The introduction presents the concept and the reasons for difficulties in reading and writing, which are related with speech disorders. I separate described difficulties from the concept of dyslexia. Based on the analysis of case 16-year-old girl with alalia I show that the difficulties in learning reading and writing skills are the result of disturbances in speech development. The case study indicates that symptoms of alalia can persist to the age of teenage and determine the life of an adult.